Evolutionary transformation of the journal. Part 5 - Michał Kokowski (Studia Historiae Scientiarum)
The article outlines the fifth phase of the development of the journal Studia Historiae Scientiarum (previous name Prace Komisji Historii Nauki PAU / Proceedings of the PAU Commission on the History of Science). A new journal website has been created. The information has been provided on the journal indexing and its availability in libraries around the world, the number of foreign authors, and the number of journal reviewers.